Cartographie de L’accessibilité et Gouvernance Locale des Infrastructures Hydrauliques dans la Commune D’avrankou Au Sud-Est du Benin - Sandé, Zannou; Odile, Dossou Guedegbe (European Scientific Journal, ESJ, 2021)
In the Municipality of Avrankou, the populations experience enormous difficulties in obtaining water supplies despite the availability of a large number of water points. This work aims to analyze the distribution of hydraulic infrastructures and their mode of management in the said Municipality. To map the availability of water points and study their management method, 115 households and 17 resource people were interviewed. Arc GIS 10.5 software was used for the spatialization of the data. The results reveal that the Municipality of Avrankou has 301 hydraulic infrastructures, of which 83 are functional and 218 are non-functional. The functional water points are made up of 42 Boreholes equipped with Human Motricity Pumps and 41 Fountains supplied by 2 Village Water Adductions. Out of the 84 villages of the Commune, only 39 villages have access to functional water points, either 46.42% and among them, 12 villages have double access to it. Thus, 45 villages would have access if the authorities repaired non-functional water points and 15 villages if other structures were built. The management methods of the hydraulic infrastructures adopted are leasing and delegated management. These management methods have enabled the town hall to mobilize resources to finance development actions. The unequal distribution of hydraulic infrastructure is proof of the lack of a regular maintenance system and the absence of spatial planning tools in this sector. To remedy this, it is therefore necessary to involve the populations more and make them responsible for the management of water points and also to repair non-functional hydraulic structures. Dans la Commune dâ€™Avrankou, les populations Ã©prouvent dâ€™Ã©normes difficultÃ©s pour s’approvisionner en eau malgrÃ© la disponibilitÃ© dâ€™une importante quantitÃ© de points dâ€™eau. Ce travail vise Ã analyser la rÃ©partition des infrastructures hydrauliques et leur mode de gestion dans ladite Commune. Pour cartographier la disponibilitÃ© des points dâ€™eau et Ã©tudier leur mode de gestion, 115 mÃ©nages et 17 personnes ressources ont Ã©tÃ© interrogÃ©s. Le logiciel Arc GIS 10.5 a Ã©tÃ© utilisÃ© pour la spatialisation des donnÃ©es. Les rÃ©sultats rÃ©vÃ¨lent que la Commune dâ€™Avrankou dispose de 301 infrastructures hydrauliques dont 83 fonctionnelles et 218 non fonctionnelles. Les points dâ€™eau fonctionnels sont constituÃ©s de 42 Forages Ã©quipÃ©s de Pompe Ã MotricitÃ© Humaine et 41 Bornes Fontaines alimentÃ©es par 2 Adductions dâ€™Eau Villageoise. Sur les 84 villages de la Commune, seulement 39 villages ont accÃ¨s aux points dâ€™eau fonctionnels soit 46,42 % et parmi eux, 12 villages y ont doublement accÃ¨s. Ainsi, 45 villages auraient accÃ¨s si les autoritÃ©s rÃ©paraient les points dâ€™eau non fonctionnels et 15 villages si on construisait dâ€™autres ouvrages. Les modes de gestion des infrastructures hydrauliques adoptÃ©es sont lâ€™affermage et la gestion dÃ©lÃ©gataire. Ces modes de gestion ont permis Ã la mairie de mobiliser des ressources pour financer les actions de dÃ©veloppement. Lâ€™inÃ©gale rÃ©partition des infrastructures hydrauliques est la preuve de lâ€™inexistence dâ€™un systÃ¨me de maintenance rÃ©gulier et de lâ€™absence des outils de planification spatiale dans ce secteur. Pour y remÃ©dier, il faut donc impliquer davantage et responsabiliser les populations pour la gestion des points dâ€™eau et rÃ©parer Ã©galement les ouvrages hydrauliques non fonctionnels.